From Basic to Breakthroughs: The Journey of Microfluidic Devices in Hydrogel Droplet Generation - Gabriela Hinojosa-Ventura; José Manuel Acosta-Cuevas; Carlos Arnulfo Velázquez-Carriles; Diego E. Navarro-López; Miguel Ángel López-Alvarez; Néstor D. Ortega-de la Rosa; Jorge Manuel Silva-Jara (Gels)
Hydrogel particles are essential in biological applications because of their distinctive capacity to retain water and encapsulate active molecules within their three-dimensional structure. Typical particle sizes range from nanometers (10–500 nm) to micrometers (1–500 µm), depending on the specific application and method of preparation. These characteristics render them optimal carriers for the administration of active compounds, facilitating the regulated and prolonged release of pharmaceuticals, including anticancer agents, antibiotics, and therapeutic proteins. Hydrogel particles can exhibit various morphologies, including spherical, rod-shaped, disk-shaped, and core–shell structures. Each shape offers distinct advantages, such as improved circulation time, targeted drug delivery, or enhanced cellular uptake. Additionally, hydrogel particles can be engineered to respond to various stimuli, such as temperature, pH, light, magnetic fields, and biochemical signals. Furthermore, their biocompatibility and capacity to acclimate to many biological conditions make them appropriate for sophisticated applications, including gene treatments, tissue regeneration, and cell therapies. Microfluidics has transformed the creation of hydrogel particles, providing precise control over their dimensions, morphology, and stability. This technique facilitates reproducible and highly efficient production, reducing reagent waste and optimizing drug encapsulation. The integration of microfluidics with hydrogels provides opportunities for the advancement of creative and effective solutions in contemporary medicine.